2017
DOI: 10.1111/emip.12139
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years After the Spellings Commission: From Accountability to Internal Improvement

Abstract: Student learning outcomes assessment has been increasingly used in U.S. higher education institutions over the last 10 years, partly fueled by the recommendation from the Spellings Commission that institutions need to demonstrate more direct evidence of student learning. To respond to the Commission's call, various accountability initiatives have been launched, profoundly reshaping how assessment has been viewed, implemented, and used in higher education. This article reviews the conceptual and methodological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…First, the question of the accountability-improvement relationship remains relevant to other Canadian provinces and other parts of the world. There has been a significant shift from the focus on accountability to evidence-based continuous improvement in quality assurance schemes (Houston & Paewai, 2013;Morest, 2009) and student learning assessment (Liu, 2017;Russell & Markle, 2017). Similarly, this study demonstrates a palpable tendency within postsecondary institutions to balance accountability and improvement to enable institutional changes.…”
Section: Concluding Thoughtsmentioning
confidence: 65%
“…First, the question of the accountability-improvement relationship remains relevant to other Canadian provinces and other parts of the world. There has been a significant shift from the focus on accountability to evidence-based continuous improvement in quality assurance schemes (Houston & Paewai, 2013;Morest, 2009) and student learning assessment (Liu, 2017;Russell & Markle, 2017). Similarly, this study demonstrates a palpable tendency within postsecondary institutions to balance accountability and improvement to enable institutional changes.…”
Section: Concluding Thoughtsmentioning
confidence: 65%
“…However, when the assessment data is collected for accountability purposes, it should not be presumed that the data would be equally applicable for improvement purposes. In regards to completing the assessment cycle (Liu, 2017), this study examined and reported whether the data for educational accountability has adequate technical quality that allows interpretation and use of student assessment data for educational improvement at the programme level.…”
Section: Discussionmentioning
confidence: 99%
“…These include work of devising plans and channels for communicating assessments data internally for appropriate use at different levels, such as programme level, faculty level, or department level. Across the university, university leaders can also cultivate an assessment culture (Liu, 2017). In particular, Liu (2017) suggested faculty members work actively with assessment specialists, who can offer advice on the theory and practice on validity and validation (Brennan, 2006;Crooks, Kane & Cohen, 1996).…”
Section: Implications For Educational Leadership and Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…With increased national demand for a skilled and competent workforce, college graduates are expected, more than ever, to possess not only disciplinary skills, but also transferable skills that allow them to function effectively in a variety of settings in an increasingly globalized economy (Liu, ). Many institutions have made efforts to assess student learning of these transferrable skills to identify gaps and improve practices.…”
Section: Promoting Skills That Go Beyond Literacy and Numeracymentioning
confidence: 99%